Lifespan reference curves for harmonizing multi-site regional brain white matter metrics from diffusion MRI - Alyssa H. Zhu; Talia M. Nir; Shayan Javid; Julio E. Villalón-Reina; Amanda L. Rodrigue; Lachlan T. Strike; Greig I. de Zubicaray; Katie L. McMahon; Margaret J. Wright; Sarah E. Medland; John Blangero; David C. Glahn; et al. (Scientific Data)
Abstract Age-related white matter (WM) microstructure maturation and decline occur throughout the human lifespan, complementing the process of gray matter development and degeneration. Here, we create normative lifespan reference curves for global and regional WM microstructure by harmonizing diffusion MRI (dMRI)-derived data from ten public datasets (N = 40,898 subjects; age: 3–95 years; 47.6% male). We tested three harmonization methods on regional diffusion tensor imaging (DTI) based fractional anisotropy (FA), a metric of WM microstructure, extracted using the ENIGMA-DTI pipeline. ComBat-GAM harmonization provided multi-study trajectories most consistent with known WM maturation peaks. Lifespan FA reference curves were validated with test-retest data and used to assess the effect of the ApoE4 risk factor for dementia in WM across the lifespan. We found significant associations between ApoE4 and FA in WM regions associated with neurodegenerative disease even in healthy individuals across the lifespan, with regional age-by-genotype interactions. Our lifespan reference curves and tools to harmonize new dMRI data to the curves are publicly available as eHarmonize ( https://github.com/ahzhu/eharmonize ).